Surfactant-free emulsions stabilized by tempo-oxidized bacterial cellulose. (20th October 2016) - Jia, Yuanyuan; Zhai, Xiaoli; Fu, Wei; Liu, Yang; Li, Fei; Zhong, Cheng
Graphical abstract: Highlights: Individualized cellulose nanofibers were prepared by oxidizing bacterial cellulose in a TEMPO-mediated system. Extreme stable O/W emulsions were obtained stabilized by slightly oxidized bacterial cellulose. A combination of suitable wettability and size imparts TOBC-stabilized emulsions high stability. Abstract: In order to seek a safe, biodegradable, and sustainable solid stabilizer for food, topical and pharmaceutical emulsions, individualized cellulose nanofibers were prepared by oxidizing bacterial cellulose (BC) in a Tempo-mediated system; their ability to stabilize oil/water interface was investigated. Significant amounts of C6 carboxylate groups were selectively formed on each cellulose microfibril surface, so that the hydrophilicity was strengthened, leading to lower contact angles. Meanwhile, both the length and width of fibrils were decreased significantly, by partial cleavage of numerous numbers of inter- and intra-fibrillar hydrogen bonds. Tempo-oxidized BC (TOBC) was more effective than BC in stabilizing oil-water interface, attributing to the much smaller size. Fibril dosage and oxidation degree exerted a great influence on the stability and particle size distribution of emulsion samples. When the fibril dosage was 0.7 wt.%, the sample was so stable that it did not experience creaming and coalescence over 8 months. The 2-TOBC coated droplets showed the greatest stability, although both the zeta potential and the electric repulsion were the largest for the 10-TOBC analogue, which was manipulated by the wettability of fibrils. In addition, the stability of samples was analyzed from the viewpoint of particle size distribution. Consequently, fibril size and wettability are two counterbalanced factors influencing the stability of TOBC-stabilized emulsions; a combination of suitable wettability and size imparts TOBC-stabilized emulsion high stability. As a kind of biomass-based particle stabilizer, TOBC showed great potential applications in food, topical and pharmaceutical formulations.